ANALISIS RANCANGAN PEMBUATAN APLIKASI LAPORAN KEUANGAN PADA BUMDES AMBUNTEN TIMUR - Khoirin Azaro; Annisa Fatimah; Muhammad Rasyid Ridho (GERAKAN EDUKASI DAN MASYARAKAT NUSANTARA, 2025)
Accountability and transparency in financial management play a vital role in improving the performance of Village-Owned Enterprises (BUMDes). This research focuses on designing and providing assistance in the development of a digital financial reporting application for BUMDes Ambunten Timur, located in Ambunten District, Sumenep Regency. The application is intended to support BUMDes administrators in compiling financial reports that comply with applicable government regulations.The research methodology involves data collection through focus group discussions, field surveys, observations of business unit activities, internal team coordination, and analysis of daily financial transactions to classify debit and credit entries. The findings demonstrate that the developed application is easy to use for BUMDes administrators, including those without formal accounting expertise. In addition, participatory mentoring activities have proven effective in strengthening the administrators’ capacity to prepare accurate financial reports. Overall, this initiative is expected to enhance financial accountability, transparency, and operational efficiency within BUMDes, while also serving as a reference model for community empowerment programs facilitated by higher education institutions.